Exploring the Association Between Behavioural Modification in Response to the Prevailing Economic Crisis and Mental Health Outcomes of Nurses from Teaching Hospitals, Sri Lanka - C.P Senevirathne; L. Senarathne; M. Fernando (SAGE Publishing, 2024)
Introduction The nursing profession is a cornerstone in the healthcare workforce. Yet, it remains vulnerable to severe mental health challenges, stemming from a complex interplay of social and occupational factors. It is evident that crisis situations have profound influence on the mental-wellbeing of nurses. Objective To explore the association between behavioural modification in response to the prevailing economic crisis and mental health outcomes of nurses from teaching hospitals, Sri Lanka. Methods This cross-sectional study was carried out among nursing professionals ( n  = 261) who are employed in distinct teaching hospitals ( n  = 7) in Sri Lanka. Considering the bed-capacity of each hospital, participants were purposively selected and invited to complete an online-based self-administered questionnaire to collect demographic characteristics and lifestyle modifications to deal with the economic crisis, while Depression, Anxiety, and Stress Scale (DASS-21) a set of three self-reported scales to assess the level of depression, anxiety, and stress, was used. Data was analyzed using the SPSS 23.0 version, Descriptive analysis was performed to present frequencies of both demographic characteristics and lifestyle and symptoms of depression, anxiety, and stress, while the Chi-square test was used to determine the association between selected independent variables and mental health outcomes. A multivariate regression model was performed to determine the predictors of mental health outcomes of the study participants. Results There were a total of 261 participants, 86.2% were married, and 66.2% had children. The proportion of mild to extreme depression, anxiety, and stress were 58.2%, 65.9%, and 72.0% respectively. In response to the economic challenges, 91.6% of study participants reported reducing expenditures on general household needs, while the proportion of participants who curtailed spending on food, monthly savings, and entertainment were 75.9%, 79.3%, and 73.6% respectively. Notably, 81.6% of participants initiated the process of applying for overseas employment, and 50.6% pursued academic programs to be eligible for foreign placements. Conclusion The present study observed a higher level of depression, anxiety and stress among nurses from teaching hospitals in Sri Lanka. It was noted that nurses had taken steps to respond to financial strain by reducing essential elements of their routine. Additionally, study participants chose to seek foreign placements as a solution to the economic burden, as a result just over half of the respondents completed an academic program in order to be qualified for jobs abroad. Further, these initiatives are significantly associated with negative emotional disorders of the participants. Therefore, interventions should be implemented to promote positive mental health outcomes of nursing professionals in Sri Lanka.